DAYA SAING EKSPOR BARANG‐BARANG DARI KARET - Sony Hendra Permana; Izzaty Izzaty (Pusat Penelitian, Badan Keahlian DPR RI, 2010)
Indonesia is the second largest rubber producer in the world in which along with Thailand and Malaysia, the market share is about 70%. With the increasing of world demand for rubber planting, Indonesia is the high potential to become the country's first largest rubber producer in the world. However, although Indonesia has the largest rubber plantation area,hers quality and productivity below those 2 countries. This analysis using the Method Revealed Comparative Advantage (RCA), Acceleration Ratio (AR), and Trade Specialization Index (TSI) which hd found that rubber from Indonesia, mostly a raw natural rubber (HS 4001 and 4003), while the other products do not have a competitive advantage. Therefore, it is necessary to increase the productivity and efficiency through the expansion of planting areas, new planting trees, and the using clones superior rubber. In addition, it is necessary to develop the rubber processing industry, to gain added value both for industry in order to reach the welfare of the society.